Web-Based Village Information System Design: (Study At One of The Villages in West Java) - Faturahman, Dyas; Jamaludin, Ikbal; Suwarno, Adi; Susanto, Susanto (LPPM STMIK Mardira Indonesia, 2024)
The findings of this study indicate that the combination of intrinsic motivation and compensation has a notable impact on the performance of employees in a fashion firm located in Bandung. Consequently, these two elements can enhance employee performance concurrently. However, more factors impact employee performance that should have been investigated in this study. Additional elements may encompass work discipline, leadership, job stress, competency, and organizational culture. Our research underscores the pivotal role of intrinsic motivation in boosting employee performance, surpassing the influence of compensation. Employees with a strong sense of intrinsic motivation, including job satisfaction, commitment to the organization, and a drive to succeed, consistently demonstrate superior performance. However, compensation continues to be a significant issue that affects employee performance. Employees who see the company's income, benefits, and incentives as equitable and commensurate with their workload are more likely to be motivated to perform at a higher level. The importance of equitable and competitive remuneration cannot be overstated, as it enhances employee well-being, potentially boosting productivity and job excellence. Ultimately, both internal motivation and financial rewards significantly impact employee performance. However, it's crucial for management to take the lead in prioritizing strategies that enhance employee intrinsic motivation. This can be achieved through proactive implementation of programs and policies that boost job satisfaction, foster devotion to the organization, and cultivate a strong drive to achieve. Regular evaluation and modification of compensation schemes to ensure equity and competitiveness are also essential. By focusing on these two factors, firms can achieve maximum staff performance, leading to enhanced overall productivity and success.